Blood pressure and heart rate responses to orthostatic challenge and Valsalva manoeuvre in mild cognitive impairment with Lewy bodies. (7th April 2022) - Hamilton, Calum A.; Frith, James; Donaghy, Paul C.; Barker, Sally A. H.; Durcan, Rory; Lawley, Sarah; Barnett, Nicola; Firbank, Michael; Roberts, Gemma; Taylor, John‐Paul; Allan, Louise M.; O'Brien, John; et al.
Abstract: Objectives: Orthostatic hypotension is a common feature of normal ageing, and age‐related neurodegenerative diseases, in particular the synucleinopathies including dementia with Lewy bodies. Orthostatic hypotension and other abnormal cardiovascular responses may be early markers of Lewy body disease. We aimed to assess whether abnormal blood pressure and heart rate responses to orthostatic challenge and Valsalva manoeuvre would be more common in mild cognitive impairment with Lewy bodies (MCI‐LB) than MCI due to Alzheimer's disease (MCI‐AD). Methods: MCI patients ( n = 89) underwent longitudinal clinical assessment with differential classification of probable MCI‐LB, possible MCI‐LB, or MCI‐AD, with objective autonomic function testing at baseline. Blood pressure and heart rate responses to active stand and Valsalva manoeuvre were calculated from beat‐to‐beat cardiovascular data, with abnormalities defined by current criteria, and age‐adjusted group differences estimated with logistic models. Results: Orthostatic hypotension and abnormal heart rate response to orthostatic challenge were not more common in probable MCI‐LB than MCI‐AD. Heart rate abnormalities were likewise not more common in response to Valsalva manoeuvre in probable MCI‐LB. An abnormal blood pressure response to Valsalva (delayed return to baseline/absence of overshoot after release of strain) was more common in probable MCI‐LB than MCI‐AD. In secondary analyses, magnitude of blood pressure drop after active stand and 10‐s after release of Valsalva strain were weakly correlated with cardiac sympathetic denervation. Conclusions: Probable MCI‐LB may feature abnormal blood pressure response to Valsalva, but orthostatic hypotension is not a clear distinguishing feature from MCI‐AD. Key points: There is limited evidence of early autonomic function abnormalities in prodromal dementia with Lewy bodies. This may suggest that there is a variable staging of symptom onset in early Lewy body disease, rather than the deterministic 'body first' staging previously theorised.